Analysis of the Effectiveness of Learning in the Use of Learning Modules Against Student Learning Outcomes - Rahmawati, Rika; Lestari, Fitria; Umam, Rofiqul (Universitas Islam Negeri Raden Intan Lampung, 2019)
At present there are still students who have difficulty in learning, due to limited learning resources. One effort that can be done is the use of modules in learning. Modules are printed teaching materials designed to be studied independently by learning participants. This study aims to determine the effect of the use of modules on the learning outcomes of students in MTs Hasanuddin Teluk Betung. Through the analysis of diffrences in the average of mathematics learning outcomes between those who used modules and those who did not use modules. The method used in this study is experiments with quantitative exploratory levels. The basic data collection technique uses a test technique that is to determine students learning outcomes. Testing hypotheses by using the t-test statistical formula. Based on the results of hypothesis testing it was concluded that the average mathematics learning outcomes of students using modules were higher than students who did not use the module.